Junie B. Jones smells something fishy - Park, Barbara; Brunkus, Denise (New York : Random House, 1998)
Frustrated because the rules for her class's Pet Day will not let her take her dog to school, Junie B. Jones considers taking a raccoon, a worm, a dead fish, and other unusual replacements.
"A stepping stone book."
Accelerated Reader.
Accelerated Reader.
1 3 5 6 7 8 9 10 11 13 15 17 18 19 21 23 26 27 29 30 33 39
Keywords: Kindergarten -- Fiction; Schools -- Fiction; Pets -- Fiction